Analisis Penanganan Longsoran dengan Perkuatan Bored Pile (Studi Kasus: Ruas Jalan Tb. Lahung-Sp. Muara Laung Sta. 43+900) - Stephanus Alexsander; Fatma Sarie; Apria Brita P. Gawei; Lydia Dwinanda Sinaga (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
A landslide occurred on Tb. Lahung–Sp. Muara Laung Road Section Sta.43+900 experienced a slope collapse, measuring 7 m deep, along the roadside. This underscores the urgent need for effective landslide management. This study definitively sets out to determine the initial safety factor (SF) value on the landslide slope and analyze changes in safety factor (SF) value after the slope was reinforced with bored piles. Slope stability analysis was conducted using the finite element method (FEM) with Plaxis. The analysis of existing conditions yielded an initial safety factor (SF) value of 2.474. This indicates that the slope is safe; however, it is a landslide slope. The back analysis was conducted, and the SF value changed to 1,032, indicating critical slope conditions. The slope stability analysis was performed using Bishop's method to calculate the safety factor manually. The result was an SF value of 1.00, indicating that the slope is in critical condition. The slope was reinforced with bored piles that were 0.5 m diameter and 8 m long. The safety factor (SF) value increased to 1,323. The safety factor (SF) has met the requirements of SF ≥ 1.25 (SNI 8460-2017). The landslide at the study site required a total of 54 bored piles.